Pengaruh Pelapisan yang Dapat Dimakan terhadap Perubahan Warna dan Sifat Mekanik Resin Akrilik yang Disembuhkan dengan Panas yang Direndam dalam Teh Hitam (Camellia Sinensis) - Hernindya Dwifulqi; Silvia Nailani; Vinna Kurniawati Sugiaman; Theodora Adhisty Dwiarie; Maria Florensia Rosa Centifolia Bulata Dolu (Denta Journal Kedokteran Gigi, 2025)
Background: Dentures are a standard treatment option for replacing missing teeth. One of the most essential components of dentures is the denture base. However, the acrylic resin has a weakness, namely that it has porosity, which can cause water absorption and colour changes. Water absorption in the acrylic resin can affect its colour stability, flexural strength, and hardness over a specific period. Tea is a drink often consumed in Indonesia. Black tea has undergone oxidation of several polyphenolic compounds (catechins). The fermentation process results in the oxidation of simple polyphenols, where tea catechins are converted into more complex and concentrated molecules that give black tea its characteristic colour. The edible coating is a thin layer made from consumable materials that acts as a barrier. Objective: To determine the effect of edible coating on heat-cured acrylic resin denture plates on colour retention, flexural strength, and hardness after soaking in black tea. Materials and Methods: This research utilized 25 heat-cured acrylic resin plates, divided into five groups with varying soaking times for the edible coating. The plates were then soaked in black tea for 15 hours, after which testing was conducted on the color resistance, hardness, and flexural strength of the heat-cured acrylic resin plates. Results: Acrylic resin plates with chitosan have better colour retention than acrylic resin not soaked with chitosan. Meanwhile, flexural strength and hardness values between groups did not differ significantly. Conclusion: Chitosan immersion affects the colour durability of the heat-cured acrylic resin denture base without significantly decreasing the hardness and strength values.